Letnia konferencja ASAB na temat "Ewolucja sygnałów" (Berno, 20-22 VII 1994 r.) - Jabłoński, Piotr G. (Oficyna Wydawnicza Instytut Ekologii PAN, 1995)
Pages 57-59 ; 24 cm
Keywords: animal communication; congresses

Putman R. J. 1994 - Community ecology - Chapman & Hall. London, New York, Toronto, ss. 178. [ISBN 0-412-54500-4] - Uchmański, Janusz (Oficyna Wydawnicza Instytut Ekologii PAN, 1995)
Pages 97-100 : illustrations ; 24 cm
Keywords: animal communities; ecology; reviews

Maynard Smith J., Harper D. 2003 - Animal signals - Oxford University Press, Oxford, ss. 166. [ISBN 0-19-852684-9 (Hbk), 0-19-852685-7 (Pbk)] - Grüm Leszek (Centrum Badań Ekologicznych PAN, 2005)
Pages 39-41 ; 24 cm
Keywords: animal communications; animal behavior; reviews

XXXV Warsztaty Biologii Ewolucyjnej (Warszawa, 29 X 2005 r.) - Matyjasiak, Piotr (Centrum Badań Ekologicznych PAN, 2006)
Pages 35-37 ; 24 cm
Keywords: evolutionary biology; animal communications; congresses

Dice Lee - Natural communities. University of Michigan Press, 1954 - Hillbricht, Anna (Państwowe Wydawnictwo Naukowe, 1957)
Strony 173-177 ; 24 cm
Keywords: animal communities; biotic communities; biocenology; reviews; Ekologia -- Polska -- czasopisma; Ekologia -- czasopisma

Obserwacje nad zasiedlaniem dziurawca czterobocznego Hypericum maculatum Cr. przez pająki - Kajak, Anna (Państwowe Wydawnictwo Naukowe, 1961)
Pages 287-298 : illustrations ; 24 cm
Bibliographical references (page 296)
Abstract in English
Keywords: spiders; animal communities; Poland; Kampinos Forest; Araneae

W sprawie problematyki biocenotycznej - Kaczmarek, Wojciech (Państwowe Wydawnictwo Naukowe, 1956)
Pages 3-16 ; 24 cm
Bibliographical references (pages 15-16)
Keywords: animal communities; biotic communities; assotiation; biocenology

Ptaki wodne i ich rola w ekosystemie jeziornym - Dobrowolski, Kazimierz A. (Państwowe Wydawnictwo Naukowe, 1973)
Pages 353-371 : illustrations ; 24 cm
Bibliographical references (pages 368-370)
Abstract in English
Keywords: water birds; lake ecology; counting; food; animal communities

O metodyce badań zoocenotycznych w zakresie zbiorów ilościowych naziemnej fauny bezkręgowców - Kaczmarek, Maria; Kaczmarek, Wojciech (Państwowe Wydawnictwo Naukowe, 1956)
Pages 131-136 ; 24 cm
Bibliographical references (page 136)
Keywords: quantitative research; quantitative methods; animal communities; invertebrates; Invertebrata

Kryterium Beklemiszewa faunistycznej reprezentatywności prób ilościowych - Tarwid, Kazimierz (Państwowe Wydawnictwo Naukowe, 1956)
Pages 27-31 ; 24 cm
Bibliographical references (page 31)
Keywords: quantitative research; quantitative methods; statistical methods; animal communities

Arthropod communities in terrestrial ecosystems - contents - Sawoniewicz, Janusz (1947– ). Red.; Trojan, Przemysław (1929– ). Red. (Zakład Narodowy im. Ossolińskich - Wydawnictwo Polskiej Akademii Nauk, 1979)
4 s. ; 24 cm
Keywords: Poland; Arthropoda; arthropods; ecology; animal communities; terrestrial ecosystem; land ecosystem

Arthropod communities in terrestrial ecosystems - Sawoniewicz, Janusz (1947– ). Red.; Trojan, Przemysław (1929– ). Red. (Zakład Narodowy im. Ossolińskich - Wydawnictwo Polskiej Akademii Nauk, 1979)
4 s. ; 24 cm
Keywords: Poland; Arthropoda; arthropods; ecology; animal communities; terrestrial ecosystem; land ecosystem

The phenological interchange of bird communities in agricultural biotopes in the eastern part of the Masovian lowland region - Jabłoński, Bolesław (1937– ) (Państwowe Wydawnictwo Naukowe, 1972)
Liczbowanie stron również: 281-321
With 2 photographs, 4 diagrams, 3 graphs and 12 tables in the text
Bibliogr. p. 34-36 (314-316)
41 p. : ill. ; 24 cm
Abstracts in Polish, Russian. Nazwy taksonów także w j. łac.
Keywords: birds; animal communities; Poland; Mazowsze Plain; Masovian Plain; phenology; agricultural landscape; Aves

Wioślarki /Cladocera/ Jeziora Świtezi Nowogródzkiej - Klawir, Penia (1897-II wojna światowa) (Wolna Wszechnica Polska, 1939)
Maszynopis pracy magisterskiej
Patrz: Spraw. ŁTN 3 1948
Bibliogr. s. I-XI
[3] 103 k., XI k. : 30 cm
Keywords: Świteź (Białoruś; jezioro); Nowogródek (region); water fleas; arthropods; zoocenosis; animal communities; crustaceans; cladocerans; Cladocera; Crustacea; Arthropoda

J. Balogh - A zoocönológia alapjai. Grundzüge der zoozönologie, Budapest, 1953 - Szczepański, Andrzej (Państwowe Wydawnictwo Naukowe, 1956)
Strony 159-160
Keywords: biocenology; animal communities; biotic communities; biological productivity; reviews; Balogh János (1913-2002)

Drobne ssaki (Micromammalia) Roztocza. Cz. 1, Micromammalia wybranych biotopów Roztocza Środkowego - Ziomek, Joanna (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 1998)
The paper presents the results of investigation of the occurence of small mammals in the Central Roztocze Upland based on the catch. Mammals were caught in fifteen habitats in 108 localities during 1986–1990. The material consists of 2543 specimens belonging to 19 species.
W serii gł.: Fragmenta Faunistica, ISSN 0015-9301; t. 41, nr 8
Bibliogr. p. 120-122
P. 93-123 : ill. ; 24 cm
Abstract in English. Taxa in Latin.
Keywords: animal communities; zoocenosis; Roztocze (region); Roztochia (region); Poland; mammals; Mammalia; small mammals; Micromammalia; fauna of Roztocze

Kilka nowych lub mniej znanych w faunie polskiej gatunków pluskwiaków (Heteroptera). 3 = Einige für Polen neue oder wenig bekannte Heteropteren-Arten. 3 - Jaczewski, Tadeusz (1899–1974) (nakł. Państwowego Muzeum Zoologicznego, 1934)
Tyt. nagł.
Oznaczenie stron również: S. 147-149
3 p. ; 24 cm
abstract in German. Taxa in Latin
Keywords: animal communities; Zaleszczyki; Podolia; Ukraine; zoocenology; Poland; Heteroptera; hemipterans; Hemiptera; insects; Insecta

Materjały do fauny Cladocera i Copepoda jezior Suwalszczyzny = Beitrag zur Cladoceren- und Copepoden-Fauna der Seen des Suwałki-Gebietes - Bowkiewicz, Jan (1896–1968) (nakł. Państwowego Muzeum Zoologicznego, 1934)
Tyt. nagł.
Oznaczenie stron również: S. 143-146
4 p. : ill. ; 24 cm
abstract in German. Taxa in Latin
Keywords: ecology; Poland; animal communities; crustaceans; Crustacea; zoocenosis; biocenosis; copepods; Copepoda; arthropods; Arthropoda; stawonogi; water fleas; Cladocera

Materjały do planktonu jezior Suwalszczyzny = Zur Kenntnis des Planktons der Seen des Suwałki-Gebietes - Bowkiewicz, Jan (1896–1968) (nakł. Państwowego Muzeum Zoologicznego, 1934)
Tyt. nagł.
Oznaczenie stron również: S. 151-156
6 p. : ill. ; 24 cm
abstract in German. Taxa in Latin
Keywords: crustaceans; Crustacea; Poland; zooplankton; ecological succession; animal communities; arthropods; Arthropoda; copepods; Copepoda; water fleas; Cladocera

Ślimaki leśnictwa Sękocin - Skrzypczak, Emilia; Umiński, Tomasz (Państwowe Wydawnictwo Naukowe, 1979)
p. 21-35
bibliogr. p. 13 (33)
15 p. : ill. ; 25 cm
Abstract in Polish, English. Taxa in Latin
Keywords: Gastropoda; gastropods; snails; forest site quality; land gastropods; zoocenozy; zoocenosis; animal communities; Poland; Warsaw (region)

Mięczaki (Mollusca) rozlewisk łąkowych w Górach Świętokrzyskich - Abraszewska-Kowalczyk, Anna; Państwowe Wydawnictwo Naukowe (1951–1992); Polska Akademia Nauk. Instytut Zoologii (Państwowe Wydawnictwo Naukowe, 1986)
W serii gł. Fragmenta Faunistica, t. 30, nr 8
Bibliogr. p. 133-134
P. 121-136 : ill. ; 24 cm
Abstract in English, Russian. Taxa in Latin.
Keywords: Holy Cross Mountains; Świętokrzyskie Mountains; Poland; mollusks; molluscs; Mollusca; animal communities; zoocenosis

The environmental evaluation by synecological zooindication - a proposal of the method based on epigeic invertebrate communities - Smoleński, Marcin (1962– ); Polska Akademia Nauk. Muzeum i Instytut Zoologii (Museum and Institute of Zoology, PAS, 2001)
This paper presents an original methodological attempt at natural valorization based on the analysis of epigeic invertebrate communities. The essence of the method is in determining the proximity of the real community towards the standard one, the latter elaborated so that it is representative for the ecosystem of given type. The survey, the assessment of the natural value and the evaluation of the anthropopressure are all based on the test describing epigeic communities of invertebrates with the use of seven indices: I. Per cent share: (1) per cent share of characteristic - exclusive species F3; and total of characteristic exclusive and choosing species F3+F2; (2) the index of community uniqueness Sc; (3) the index ofcommunity stability Nc; (4) the index of species diversity H’; (5) the index of community natural quality Bc; (6) the index of dynamic heterogeneity DHt; (7) the index of habitat species capacity Pc
Bibliogr. p. 266-267
P. 251-268 ; 25 cm
Abstarct in Polish. Taxa in Latin.
Keywords: ecological indicators; mathematical models; methods; animal communities; zoocenosis; epigeic animals; epigeic fauna; research; zoocenology; zooindication

Changes in the structure of mosquito (Diptera, Culicidae) communities in the Kampinos Forest for 40 years - Wegner, Elżbieta (Zakład Narodowy im. Ossolińskich - Wydawnictwo Polskiej Akademii Nauk, 1979)
W serii gł. nr 30
Bibliogr.p. 143-144
P. 131-144 : il. ; 24 cm
Abstracts in English, Polish, Russian. Taxa in Latin
Keywords: Poland; mosquitoes; Culicidae; Kampinos Forest; ecology; phenology; animal communities; Insecta; insects; flies; Diptera; zoocenology

Analiza struktury fauny - Trojan, Przemysław (1929– ) (Muzeum i Instytut Zoologii PAN, 1992)
Bibliogr. p. 117-120
120, [1] p. : ill. ; 24 cm
Keywords: Simpson index; Shannon - Weaver index; animal communities; faunistics; research; methodology; zoology; animal ecology; faunistic analysis; fauna

O pewnych prawidłowościach w składzie jakościowym zooplanktonu jezior = Über einige Regelmässigkeiten in der Zusammensetzung des Seenzooplanktons - Bowkiewicz, Jan (1896–1968) (nakł. Państwowego Muzeum Zoologicznego, 1938)
Liczbowanie stron również: S. 345-414
Z 33 tabelami
Bibliogr. p. 65-66 (409-410)
70 p. ; 25 cm
Abstract in German. Taxa in Latin
Keywords: Suwalsko-Augustowskie, Pojezierze; Poland; animal communities; crustaceans; Crustacea; zoocenosis; biocenosis; copepods; Copepoda; arthropods; Arthropoda; water fleas; Cladocera